The Attractiveness of Brand Ambassadors in Increasing Purchase Intention among Instagram Followers @skintificid - Noviana, Laela (Universitas Muhammadiyah Mataram, 2024)
Abstract:Competition in the beauty industry in Indonesia is increasingly competitive. This is in line with the development of beauty trends and the high public interest in beauty products. Companies are required to implement appropriate marketing strategies to increase sales, one of which is through the use of brand ambassadors. This research aims to determine the influence of brand ambassador attractiveness on product purchase intention among @skintificid Instagram followers. This research uses a quantitative approach with survey methods. Data collection was carried out by distributing questionnaires to 100 respondents who had been selected using non-probability sampling techniques. The data analysis techniques used are simple regression analysis, t hypothesis test, and coefficient of determination. The results of this research show that the attractiveness of brand ambassadors has a significant effect on product purchase interest among @skintificid Instagram followers by 23.8%. The remaining 76.2% was influenced by other factors outside this research. These results show that the higher the attractiveness of the brand ambassador, the greater the purchase intention. In line with the basic assumption of the source of attractiveness theory that attractiveness can positively influence a person's behavior in making purchases.